1995
DOI: 10.1111/j.1524-4725.1995.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Necrosis, Telangiectatic Matting, and Hyperpigmentation following Sclerotherapy Etiology, Prevention, and Treatment

Abstract: After studying the following article, participant should be able to: 1. Understand the definition and potential causes of cutaneous necrosis, telangiectatic matting, and hyperpigmentation following sclerotherapy. 2. Advise patients prior to treatment on the common risks involved in sclerotherapy and to advise them on the relative incidence. 3. Understand the concept of minimal sclerosant concentration and how it can help the physician to choose sclerosing solution concentrations to minimize risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
104
3
25

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 63 publications
2
104
3
25
Order By: Relevance
“…Technique-related measures to prevent this complication include using the minimum sclerosant concentration, small volumes and low pressure when treating a vein. Telangiectic matting usually is transient and resolves 3-12 months posttreatment [5,12] . Nevertheless, matting can be also permanent [12] .…”
Section: Safety Of Detergentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Technique-related measures to prevent this complication include using the minimum sclerosant concentration, small volumes and low pressure when treating a vein. Telangiectic matting usually is transient and resolves 3-12 months posttreatment [5,12] . Nevertheless, matting can be also permanent [12] .…”
Section: Safety Of Detergentsmentioning
confidence: 99%
“…The cause of matting remains unclear. It has been suggested that this represents either dilatation of pre-existing subclinical vessels or angiogenesis due to inflammatory processes and vascular obstruction [12] . It appears as a patchy pigmentation with onset 4-6 weeks posttreatment.…”
Section: Safety Of Detergentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The larger the varicosities are, the more likely it is that the side effects will occur. 24,25 Occasionally, localized thrombi become painful and require stab-wound transcutaneous evacuation with manual compression of the vein. This is done with local anesthetic infiltration of the skin under sterile conditions.…”
Section: Complicationsmentioning
confidence: 99%